1976
DOI: 10.1139/g76-004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effects and Genetic Effect × Year Interactions at Three Gene Loci in Sublines of a Maize Inbred Line

Abstract: "Isogenic" lines of maize (Zea mays L.) inbred B14, differing by single marker genes and chromosome segments linked to these genes, were used to study gene action in the inheritance of 10 plant, ear, and grain characters. The 27 genotypes representing all combinations of the homozygous and heterozygous genotypes at three loci, rp, wx, and ws, were evaluated for three years. Highly significant differences among genotypes were observed for eight characters; genotype × year interactions were highly significant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
4
2
8
Order By: Relevance
“…This contradicted the findings of Russell (1976), who indicated no significant genotype × year interaction for plant height or ear attachment height. The genotype × year interaction for the length of the main tassel axis above the lowest side-branch was significant at 5%, while those for the length of the main tassel axis above the uppermost branch, for stalk diameter and for leaf number were not.…”
Section: Resultscontrasting
confidence: 79%
“…This contradicted the findings of Russell (1976), who indicated no significant genotype × year interaction for plant height or ear attachment height. The genotype × year interaction for the length of the main tassel axis above the lowest side-branch was significant at 5%, while those for the length of the main tassel axis above the uppermost branch, for stalk diameter and for leaf number were not.…”
Section: Resultscontrasting
confidence: 79%
“…The standard Cockerham model was fit to the data to estimate additive, dominance, and epistatic effects. Russell (1976) found that 87, 27, 47,15,23, and 30% of the additive, dominance, additive x additive, additive x dominance, and dominance x dominance effects were significant at the 5% level, indicating that even at the population level, loci were interacting fairly frequently. This study also demonstrates the pleiotropic effect of loci.…”
Section: Measured Genotypesmentioning
confidence: 97%
“…Together, these two studies bring out the salient features of the analyses. Russell (1976) developed B 14 isolines of the 27 genotypes possible for three loci with two alleles. The experiment was grown for three years at one location and data were collected for 10 traits.…”
Section: Measured Genotypesmentioning
confidence: 99%
“…Os estudos sobre os componentes da variação genética indicam que esses caracteres são controlados predominantemente por genes com efeitos aditivos (GARDNER et ai., 1953;STUBER et al, 1966;RUSSELL & EBERHART, 1970;HALLAUER, 1971;SUBANDI & COMPTON, 1974;RUSSELL, 1976;HALLAUER & MIRANDA FIRO, 1988); com relação ao grau médio de dominância, estimativas indicam a presença de dominância parcial relativa à maior altura de planta e de espiga, reforçando assim a hipótese de predominância de genes aditivos (COMSTOCK & ROBINSON, 1948;ROBINSON et al, 1949;GARDNER & LONNQUIST, 1959), demonstrando que esses caracteres podem ser reduzidos através do uso de seleção recorrente. ARAÚJO (1992), trabalhando com a população ESALQ PB-1, no quinto ciclo de seleção divergente para maior (E+) e menor (E-) altura de espiga, estimou a variância genética aditiva para altura de espigas na ordem de 167,35 e 68,85 (cm/planta) 2 , respectivamente.…”
Section: Altura De Espigasunclassified